Transport of monoglucuronosyl and bisglucuronosyl bilirubin by recombinant human and rat multidrug resistance protein 2 - Kamisako, Toshinori; König, Jörg; Keppler, Dietrich (Hepatology, 2003)
The secretion of bilirubin conjugates from hepatocytes into bile represents a decisive step in the prevention of hyperbilirubinemia. The bilirubin conjugates, monoglucuronosyl bilirubin (MGB) and bisglucuronosyl bilirubin (BGB), were previously suggested to be endogenous substrates for the apical multidrug resistance protein (MRP2), a member of the adenosine triphosphate (ATP)-binding cassette family of transporters (symbol ABCC2), also termed canalicular multispecific organic anion transporter. We have characterized this ATP-dependent transport using membrane vesicles from human embryonic kidney (HEK) cells expressing recombinant rat as well as human MRP2. MGB and BGB, 3H-labeled in the glucuronosyl moiety, were synthesized enzymatically with recombinant UDP-glucuronosyltransferase 1A1, and stabilized with ascorbate. Rates for ATP-dependent transport of MGB and BGB (0.5 μmol/L each) by human MRP2 were 183 and 104 pmol × mg protein−1 × min−1, respectively. Km values were 0.7 and 0.9 μmol/L for human MRP2, and 0.8 and 0.5 μmol/L for rat MRP2, with MGB and BGB as substrates, respectively. Leukotriene C4 and 17β-glucuronosyl estradiol, which are both known high-affinity substrates for human MRP2, inhibited [3H]MGB transport with IC50 values of 2.3 and 30 μmol/L, respectively. Cyclosporin A competitively inhibited human and rat MRP2-mediated transport of [3H]MGB, with Ki values of 21 and 10 μmol/L, respectively. Our results provide direct evidence that recombinant MRP2, cloned from rat as well as human liver, mediates the primary-active ATP-dependent transport of the bilirubin conjugates MGB and BGB.